2019
DOI: 10.3390/catal9080686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorine-Containing VOCs on Silver Migration and Sintering in ZSM-5 Used in a TSA Process

Abstract: Silver nanoparticles are currently one of the most studied nanostructured nanomaterials. Because nanoparticle size and dispersion act together in determining a material’s physical and chemical properties, there is a continuous quest to develop size-controlled synthesis methods. Nonetheless, the instability of the nanometer-sized particles, which is caused by their tendency to aggregate irreversibly into larger particles, remains a recurrent problem. The use of confining scaffolds, such as the regular system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Inset: Ag 3d level from silver foil treated by sputtering cycles of Ar + , in which the arrows indicate the presence of plasmon features. Parts a and b were adapted with permission from ref . Copyright 2019 MDPI AG.…”
Section: Resultsmentioning
confidence: 99%
“…Inset: Ag 3d level from silver foil treated by sputtering cycles of Ar + , in which the arrows indicate the presence of plasmon features. Parts a and b were adapted with permission from ref . Copyright 2019 MDPI AG.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from water vapor, recent investigations also indicate that organic species containing chlorine show a measurable poisoning effect on Ag-ZSM-5 with regard to Xe adsorption 39 . It can be concluded that proper protection of the adsorption bed from species attacking the active sorption sites will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from water vapor, recent investigations also indicate that organic species containing chlorine show a measurable poisoning effect on Ag-ZSM-5 with regard to Xe adsorption 35 . It can be concluded that proper protection of the adsorption bed from species oxidizing silver will be required.…”
Section: Discussionmentioning
confidence: 99%